Implementation of White Hat SEO Techniques to Improve Digital Promotion of Village Potentials Product (Case Study: Kebun Kelapa Village) - Akbar, Ahmad; Suheri, Suheri; Sinaga, Josua Betrand (International Conference on Sciences Development and Technology, 2023)
This paper investigates the implementation of white hat SEO (search engine optimization) techniques to promote village potential products online, using the case study of coconut distributors in Kebun Kelapa Village, Medan, Indonesia. The specific SEO techniques explored include keyword optimization, quality content creation, meta tag and description refinement, alt text for images, internal linking between related posts, and optimizing for mobile devices. Initial results show that targeted keyword usage, organizing site structure, and highlighting unique value propositions in content can effectively improve site visibility and search engine rankings. Further analysis on user engagement and lead generation conversion is still required. Adoption of white hat SEO strategies has promising potential for rural businesses to expand their reach via digital platforms.